Time for Action: Verbal Action Cues Influence Temporal Binding - Damen, Tom G. E.; van Baaren, Rick B.; Dijksterhuis, Ap (Frontiers in Psychology, 2020)
Prior research has shown that our perception of time is compressed when we volitionally perform actions, a phenomenon referred to as temporal binding. In three studies we investigated the degree to which contextual cues that signaled other agents and related to actions would influence binding, given that those cues may affect individual’s feelings of independent action performance. Participants heard action verbalizations that did or did not match actions that participants had already begun performing. Participants’ time estimates of the intervals between action initiations and action effects were higher on trials in which they heard verbalizations that matched their ongoing actions, and lower on trials in which the verbalizations and actions did not match. Such effects did not occur when participants passively observed actions and effects being caused by the computer. These results show that the compatibility of action cues with ongoing actions influence temporal binding effects, suggesting that they influence our feelings of having been an independent agent.